The construction of the teacher's subjectivity: implications for teaching today (Research, Society and Development, 2020)
Teaching should be one of the most relevant professions for today's society, but what has been observed is its decline and devaluation. The consolidation of this profession in the context of Brazilian education was marked by advances and setbacks that sometimes threatened the interests and projects of a ruling class. In this context, the teacher was also constituting himself, as a subject in the social as a professional of Education, based on what he believed and conceived as important for the construction of his subjectivity. Therefore, this paper aims to understand how the construction of the subjectivity of this teacher has occurred in the course of the professional teaching career in the Brazilian context. Through a theoretical study of a qualitative nature, a historical survey of Education and the teacher was first made in the Brazilian context, in a second moment to understand how could the construction of the subjectivity of this professional to date. Given the findings, it was understood that this education professional was / is subject to the effects of political / economic interests / organizations, which has resulted in the construction of a subjectivity absorbed by a system that strives for productivity to the detriment of intellectual growth itself. This construction takes place in an existential territory where there is a diversity of bonds, relationships and actions, so understanding these different processes of subjectivation in the context of teaching, reflecting and dialoguing about them can open doors to invent other ways of being and work as teacher.